2014
DOI: 10.1097/prs.0000000000000589
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Considerations Regarding the Location and Boundary of the Depressor Anguli Oris Muscle with Reference to Botulinum Toxin Injection

Abstract: These results suggest that the fan-shaped area bounded by LP2, LP3, and the mandibular border is the safest and most effective depressor anguli oris muscle injection site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 8 publications
1
43
0
1
Order By: Relevance
“…An anatomical study investigated the position and relation of the depressor anguli oris muscle to bony landmarks and other facial muscles. The authors found that the point at which the lateral border of the depressor anguli oris and the mandibular border meet is located 22.6 AE 8.6 mm lateral and 20.8 AE 8.3 mm inferior to the modiolus; at this point, it interlaces with the adjacent platysma and this is apparently where it receives its motor contribution [16]. A description of muscular orientation and anatomic relation of depressor anguli oris and platysma was carried out also by other authors [17].…”
Section: Discussionmentioning
confidence: 99%
“…An anatomical study investigated the position and relation of the depressor anguli oris muscle to bony landmarks and other facial muscles. The authors found that the point at which the lateral border of the depressor anguli oris and the mandibular border meet is located 22.6 AE 8.6 mm lateral and 20.8 AE 8.3 mm inferior to the modiolus; at this point, it interlaces with the adjacent platysma and this is apparently where it receives its motor contribution [16]. A description of muscular orientation and anatomic relation of depressor anguli oris and platysma was carried out also by other authors [17].…”
Section: Discussionmentioning
confidence: 99%
“…The appearance of the aging in the perioral region has many reasons, one of which is the drooping of the corner of the mouth, related to Depressor anguli oris muscle. Dropped mouth corner may lead to a sad and tired expression which is a common complaint for the patients referred for facial rejuvenation [11]. Botulinum toxin injection into Depressor anguli oris muscle is the current treatment modality for elevation of mouth corner.…”
Section: Discussionmentioning
confidence: 99%
“…To successfully perform the BTX injection, it is crucial to understand the stereoscopic anatomy of the face [2,5,7,[9][10][11][12][21][22][23]. Therefore, it is vital that untrained students, or trainees in particular, should understand anatomy prior to clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Skin (47) right half of skin , left half of skin creases (19) feet of crow skin creases, baggy lower eyelid skin c., blepharochalasis skin c., bunny lines skin c., fastoon skin c., glabellar frown line skin c., glabellar transverse line skin c., horizontal forehead lines skin c., horizontal upper lip line skin c., jowl skin c., labiomandibular fold skin c., marionette line skin c., mentolabial c. skin c., midcheek furrow skin c., nasojugal groove skin c., nasolabial fold skin c., palpebromalar groove skin c., preauricular lines skin c., tear trough skin c. surface metopion, glabella, sellion, rhinion, subnasale, stomion, mid lower landmarks lip point, pogonion, gnathion, frontal eminence, eurion, interciliary (22) point located on infraorbital notch, lateral orbital rim at the level of lateral canthus, zygomatic porint lacated on outer orbital region, zygion, alare, midpoint of nasolateral fold between alare and cheilion, gonion, cupid blow's peak, cheilion, lower lip points, lateral chin point located 2 cm to pogonion lip (4) vermillion border, lip, oral commissure, philtrum ligament (7) mandibular retaining lig, zygomatic cutaneous lig, zygomatic lig, orbital retaining lig, lateral orbital thickening, masseteric cutaneous lig, superior temporal septum anatomical layer of face (1) Skin thickness bone (1) bone muscle (31) frontalis m., procerus m., orbicularis oculi m.*, corrugator supercilii m.*, depressor supercilii m.*, orbicularis oris m., depressor anguli oris m.*, risorius m.*, zygomaticus major m.*, zygomaticus minor m.*, levator labii superioris m.*, levator labii superioris alaeque nasi m.*, depressor labii inferioris m.*, modiolus m., mentalis m.*, masseter m.*, temporalis m.*, platysma artery (10) dorsal nasal a., inferior labial a., lateral nasal a., nasal septal br, superior labial a., supraorbital a., supratrochlear a., inferior a.lar branch, facial a., columellar a. vein (10) angular v., inferior labial v., inferior palpebral v., intercanthal v., lateral nasal v., sentinel v., superior palpebral v., supraorbital v., supratrochlear v., facial v. nerve (10) auriculotemporal n., buccal n., external nasal branch of ophthalmic n., infraorbital n., infratrochlear n., mental n., supraorbital n., supratrochlear n., zygomaticofacial n., zygomaticotemporal n. gland (2) submandibular gland, parotid gland fat compartments (6) jowl fat comp., lateral malar fat comp., medial malar fat comp., temporal fat comp., nasolabial fat comp., infraorbital fat comp. Injection points of Botulinum rebalancing, crow s feet, infraorbital wrinkles, the botulium toxin (19) horizontal Supplementary 1.…”
Section: Conflict Of Interestmentioning
confidence: 99%